Constitutional Judges: What Powers Does the House of Representatives Have? - Wijayanti, Septi Nur; Saraswati, Retno; Addy Listya Wardhani, Lita Tyesta; Iswandi, Kelik; Surana, Tanu (Jurnal Media Hukum, 2000)
The House of Representatives did not extend the term of constitutional judge Aswanto on September 29, 2022, because Aswanto regularly nullified laws that they passed. This action was taken against the Indonesian legal system with the House of Representatives' authority to remove constitutional judges' and constitutional judges' independence. Accordingly, this paper will employ normative research approaches to assess the House of Representatives' influence over Constitutional Judges. The findings revealed that the Supreme Court, the President, and the House of Representatives proposed the constitutional judges. Each proposed institution is given the ability to nominate and choose constitutional judges. Meanwhile, the dismissal of constitutional judges is governed by Article 24C paragraph (6) of the 1945 Indonesian Constitution. Dismissal of constitutional judges is determined by Presidential decree at the request of the chief of the constitutional court.  As a result, the House of Representatives’ decision to dismiss constitutional judge Aswanto violates the Indonesian Constitution.